2011
DOI: 10.1590/s0074-02762011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological characterization of a densovirus isolate that affects dengue virus infection

Abstract: Brevidensoviruses have an encapsidated, single-stranded DNA genome that predominantly has a negative polarity. In recent years, they have received particular attention due to their potential role in the biological control of pathogenic arboviruses and to their unnoticed presence in cell cultures as contaminants. In addition, brevidensoviruses may also be useful as viral vectors. This study describes the first genetic and biological characterization of a mosquito densovirus that was isolated in Brazil; moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Reference densovirus strains were selected after blasting the NCBI NT database with a 398 bp fragment assembled with the small RNAs. Numbers in parentheses indicates the reference number of the particular virus stain [14,15,16,17,18,19,20,21,22]. The virus strain identified in this work has been assigned the name Culex tritaeniorhynchus densovirus YN2009 (indicated by a solid arrow).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference densovirus strains were selected after blasting the NCBI NT database with a 398 bp fragment assembled with the small RNAs. Numbers in parentheses indicates the reference number of the particular virus stain [14,15,16,17,18,19,20,21,22]. The virus strain identified in this work has been assigned the name Culex tritaeniorhynchus densovirus YN2009 (indicated by a solid arrow).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the evolutionary status of the densovirus identified here, a phylogenetic tree was generated with Mega 4.0 using maximum parsimony and bootstrap 500 methods (Figure 4). The reference densovirus strains [14,15,16,17,18,19,20,21,22] were downloaded from GenBank after blasting the NT database with a 398 bp segment assembled from the small RNAs. The phylogenetic tree obtained infers that newly identified Culex tritaeniorhynchus densovirus YN2009 is a close relative of the mosquito densoviruses prevalent in South and Southwest China.…”
Section: Phylogenetic Analysis Of the Newly Identified Densovirusmentioning
confidence: 99%
“…aegypti egg densities [129]. A direct inhibitory effect of MDVs on arboviral replication in cell lines has also been shown [130,131,132] which could work synergistically with pathogenic effects on the mosquito vector. However, co-infection of MDV and CHIKV in adult Ae.…”
Section: Releasing Mosquitoes For Disease Controlmentioning
confidence: 99%
“…An increasing number of arthropod-specific viruses (ASVs) are being discovered in haematophagous arthropods over the world [8], and there is a growing interest on mesoniviruses interactions with viruses of public health concern to develop strategies that could curb arbovirus transmission through dual infection and competition, as implemented with the Wolbachia mediated strategy [9]. Some studies suggested for instance that ISVs negatively affect the fitness of West Nile (WNV) [10][11][12] and dengue (DENV) [13,14] viruses in the mosquito, while other studies demonstrated that there is no effect [15] or even an enhancing effect [11]. However, there are still few studies on mesoniviruses phenotypic behaviour in mosquito vectors.…”
Section: Introductionmentioning
confidence: 99%